Development of kalamansi flavored sports drink - Lao, Cielindo Paul L.
The aim of the study was to develop a locally formulated sports drink utilizing calamansi flavor. The first phase of this study dealt with the selection an incorporation of a most acceptable calamansi-flavor concentration into the sports drink basal medium. Results of the consumer acceptability test showed that 0.06% calamansi flavor was the most acceptable calamansi flavor concentration. Consumer acceptability tests described the calamansi-flavored sports drink as having a slightly strong calamansi aroma, slightly strong calamansi flavor strength, slightly strong sweet taste, ideal sour taste, ideal degree of tartness and aftertaste. General acceptability rating was "like moderately". The sports drink basal medium with the most acceptable calamansi flavor had the following physico-chemical characteristics: a pH value of 4.30, a TSS of 9.34° brix and titrable acidity of 0.51%, expressed as citirc acid. The second phase of this study dealt with the selection and incorporation of the most acceptable calamansi flavor. Pre-judging of 6 different colors, using the Munsell Book of Colors, was done before actual color incorporation into the basal medium. The colors used in the pre-judging were: 5Y 8/8, 5Y 8/10, 5Y 8/12, 5GY 8/6, 5 GY 8/8 and 5GY 8/10. Colors 5Y 8/10, 5GY 8/6, and 5GY 8/10 were the top three colors judged as the most acceptable calamansi color for the calamansi-flavored sports drink. These three colors were simulated to determine their color concentratons using McCormick yellow and green food colors containing FD&C Yellow No.5 and FD&C Green No.3, respectively. Results of the consumer acceptability tests showed that the calamansi-flavored sports drink with color 5GY 8/10 was the most acceptable. The consumer acceptability test characterized the most acceptable calamansi-flavored sports drink with color 5GY 8/10 as having a slightly yellowish green color, s slightly strong calamansi aroma, a slightly pronounced calamansi flavor, a strong sweet and slightly strong sour tastes, an ideal tartness level and a slightly weak aftertaste. The general acceptability rating was "like moderately". The most acceptable calamansi-flavored and colored-sports drink had the following physico-chemical characteristics: a pH value of 4.30, a TSS value of 9.75°bx and a % TA of 0/51% expressed as citric acid. The third phase involved the storage study formulated calamansi-flavored and yellowish green-colored sports drink. The storage study was conducted by storing the calamansi-flavored and yellowish green-colored sports drink samples at 5°C and 28°C in a 400 ml glass bottles. Physico-chemical tests and microbiological examination were done after 3 days foa a 16-day storage period. There were no significant changes in the physico-chemical and microbiological qualities of the calamansi-flavored and colored sports drink samples at 5% level of significance stored at 5°C and 28°C during the 16-day storage period. The calamansi-flavored and yellowish green-colored sports drink samples had the following physico-chemical characteristics: a pH value of 4.30, a TSS value of 9.29, and a % TA value of 0.52%. Microbiological examinations results showed that the TPC and YMC of the calamansi-flavored and yellowish green-colored sports drink samples stored at 5°C and 28°C were <10 cfu/ml, respectively during the course of the 16-day storage period. There was no significant change in the TPC and YMC at 5% level of significance during the 16-day storage period. The fourth phase of the study dealt on the cost analysis of the formulated calamansi-flavored and yellowish green-colored sports drink. Analysis showed that the actual cost of producing the sports drink contained in a 400-ml gass bottle was P10.14/bottle. A 10% mark-up would give a suggested retail price of P11.28/bottle. This would mean 24.8% saving against the leading commercial brand.